Global Trends 2015: a dialogue about the future with nongovernment experts - Intelligence Council, National (Comentario Internacional: Revista del Centro Andino de Estudios Internacionales, 2016)
In undertaking this comprehensive analysis, the NIC worked actively with a range of nongovernmental institutions and experts. We began the analysis with two workshops focusing on drivers and alternative futures, as the appendix describes. Subsequently, numerous specialists from academia and the private sector contributed to every aspect of the study, from demographics to developments in science and teéhnology, from the global arms market to implications for the United States. Many of the judgments in this paper derive from our efforts to distill the diverse views expressed at these conferences or related workshops.